SYNTHESIS AND CHARACTERIZATION OF IONIC LIQUIDS AS CATALYSTS FOR BIODIESEL PRODUCTION FROM WASTE COOKING OIL - ULLAH, ZAHOOR (2017)
Biodiesel is relatively a fashionable word nowadays because it is purportedly environmentally friendly and is made from renewable resources (vegetable oils or animal fats). According to researchers, waste cooking oil (WCO) is a promising source for biodiesel production.